PERAN BUDAYA ORGANISASI MEMODERASI PENGARUH DISIPLIN DAN KOMITMEN ORGANISASI TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI UPT DISDIKPORA KECAMATAN BATANG - 11.52.02.0115, Insah Palupi (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study is aimed to analyze the organizational culture role of moderating influence of discipline and organizational commitment on the performance of Public Primary School Teachers at UPT Disdikpora Batang.In this study population is 338, whereas samples taken a number of 115 respondents with a purposive sampling method. By the criteria of minimum education level of S1, at least 30 years of age, years of service at least 10 years, rank / group at least class III and already citified. Measurements using a Likert 5 alternative scale. Alternative instrument used is the validity and reliability. Classical assumption used normality test, multikolonieritas test and heteroskedasticity test, While the test model used is the coefficient of determination (RÂ²) dan F test (anova test). The hypothesis test used in this study used regression analysis with t criteria test frequency distribution for the level of significance (Î±) 5%.The results showed the variables of discipline, organizational commitment and organizational culture collectively have the same effect as 67.6% of teachers performance, while 32.4% influenced by other variables not included in the study. Based on research results can be summarized as follows: (1) Discipline has positive and significant impact on performance. (2) Organizational commitment has positive and significant impact on performance. (3) Organizational culture has positive and significant impact on performance. (4) Organizational culture has not role of moderating influence of discipline on the performance. (4) Organizational culture has not role of moderating influence of organizational commitment on the performance.Keywords: Discipline, Organizational Commitment, Organizational Culture and Teacher Performance